Optimal electric-distribution-grid planning considering the demand-side flexibility of thermal building systems for a test case in Singapore - Troitzsch, Sebastian; Sreepathi, Bhargava Krishna; Huynh, Thanh Phong; Moine, Aurelie; Hanif, Sarmad; Fonseca, Jimeno; Hamacher, Thomas (Applied energy, 2020)
•Integrated planning of electric grids and operation of thermal building systems.•Considers the peak shaving potential due to demand side flexibility.•Integrated problem formulated as a single-stage, mixed-integer quadratic program.•Tested for a real-world, green-field test case based on a district in Singapore.•Up to 36.3% reduction in investment cost and 0.81% reduction in total cost. The planning of electric distribution grids aims at designing the most cost-efficient grid topology, while ensuring sufficient maximum capacity in the case of peak load conditions. With the advent of demand-side flexibility, there is the opportunity to reshape peak loads such that the investment cost of the electric grid decreases, in exchange for a minor increase in the operating cost. To this end, there exists a gap in formulating the trade-off between investment cost and operating cost, and a unsatisfactory understanding of the potential cost savings. This paper formulates a numerical optimization problem for the planning of the electric distribution grid, which incorporates the demand-side flexibility from thermal building systems, e.g., heating, ventilation and air-conditioning systems. The problem is formulated as a single-stage, mixed-integer quadratic program and aims at minimizing the investment cost for the grid along with the operating cost of the flexible loads. This is subject to the fixed electricity demand and thermal-comfort constraints of building occupants. The approach is tested on a district planning test case based in Singapore, where the results show reductions of up to 36.3% in investment cost and reductions of up to 0.81% in total annualized cost. Urban planning authorities, developers and utility companies can all benefit from the presented approach to make optimized investment decisions. For building operators, the results point to the need to adopt control systems for demand-side flexibility.